2010
DOI: 10.1186/1471-2407-10-449
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping breast cancer cell lines EM-G3, HCC1937, MCF7 and MDA-MB-231 using 2-D electrophoresis and affinity chromatography for glutathione-binding proteins

Abstract: BackgroundTransformed phenotypes are common to cell lines derived from various cancers. Proteome profiling is a valuable tool that may reveal uncharacteristic cell phenotypes in transformed cells. Changes in expression of glutathione S-transferases (GSTs) and other proteins interacting with glutathione (GSH) in model cell lines could be of particular interest.MethodsWe compared the phenotypes of breast cell lines EM-G3, HCC1937, MCF7 and MDA-MB-231 using 2-D electrophoresis (2-DE). We further separated GSH-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…These factors are biologically active and could also display effects on breast cancer cell line EM-G3. EM-G3 cells are not able to express stem cell and luminal marker K19 in vitro, which was demonstrated earlier (Mladkova et al 2010). This observation was confirmed by us in this study and even extended in conditions of co-cultures that were otherwise proven to be effective in K19 induction in keratinocytes.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…These factors are biologically active and could also display effects on breast cancer cell line EM-G3. EM-G3 cells are not able to express stem cell and luminal marker K19 in vitro, which was demonstrated earlier (Mladkova et al 2010). This observation was confirmed by us in this study and even extended in conditions of co-cultures that were otherwise proven to be effective in K19 induction in keratinocytes.…”
Section: Discussionmentioning
confidence: 68%
“…We selected the EM-G3 cell line because it was established from a tumor expressing keratin 19-marker of stem and luminal cells-but this line was completely negative for the marker in vitro. However, when in vitro cultured EM-G3 cells were grafted to the mouse, limited expression of keratin 19 reoccurred (Brozova et al 2007;Mladkova et al 2010). Based on our observations, we expected the microenvironment to play a role on the differentiation pattern of these cells.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…[25][26][27][28][29] It was previously reported that MDA-MB-231 cells do not express P-gp under normal conditions, and where the MDR1 genes (mdr1 mRNA) [30][31][32][33] as well as MRP-1 and BCRP 31) were barely detected; rather the cell expresses P-gp only after a long period of incubation with the drug 31) or when transduced with the MDR1 gene, 34) or under exposure to hypoxic conditions. 35) In MDA-MB-231 cells, the activity of GST, Bcl-2 protein which protects the cell from programmed death and detoxification enzyme cytochrome P450 that rapidly metabolize and inactivate the internalized drugs [36][37][38] would be the possible factors mediating the resistance to DOX. Therefore, it is entirely possible that the resistance of G-I cells to DOX is independent of the expression of efflux pumps, and that other MDR proteins present in the cell cytosol or in the nuclei (GST, TS, Topo II etc.)…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 and MDA-MB-231 are the most common cell lines used in breast cancer research. These cells both originated from pleural effusions and belong to subtypes of metastatic lobular carcinoma [2]. In principal, the MCF-7 cell line serves as a model of ER+ breast cancers because it expresses oestrogen receptor (ER), making these cells sensitive to oestrogen [3, 4], whereas the MDA-MB-231 cell line neither expresses hormone receptors nor human epidermal growth factor receptor-2 (HER-2), thus this cell line is used as a model of triple negative breast cancer (TNBC) [2].…”
Section: Introductionmentioning
confidence: 99%